Hubungan Metode Mengajar Dosen Terhadap Motivasi Belajar Mahasiswa DIII Keperawatan Akper Hermina Manggala Husada Jakarta - Junita Maratur Silitonga; Ria Anugrahwati (Universitas Malahayati Lampung, 2025)
ABSTRACT Teaching methods are the methods used by lecturers in establishing relationships with students during teaching. This study was conducted with the purposes to determine the relationship between lecturers' teaching methods and the learning motivation of DIII Nursing students in AKPER Hermina Manggala Husada Jakarta. This study used a cross sectional approach. The sampling technique used purposive sampling technique. The number of samples in this study was 270 respondents. The analysis used was univariate and bivariate analysis. The results showed that there was a relationship between teaching methods based on providing information and the intrinsic learning motivation of DIII Nursing students and there was a relationship between teaching methods based on providing information and the extrinsic learning motivation of DIII Nursing students. There was a relationship between teaching methods based on problem solving and the intrinsic learning motivation of DIII Nursing students and there was a relationship between teaching methods based on problem solving and the extrinsic learning motivation of DIII Nursing students. There was a relationship between teaching methods based on assignments and the intrinsic learning motivation of DIII Nursing student and there was a relationship between assignment-based teaching methods and extrinsic learning motivation of DIII Nursing students at AKPER Hermina Manggala Husada Jakarta. In conclusion, the findings highlight thatdeveloping a lecture curriculum and making teaching methods effective in the learning process is important to increase student learning motivation. Keywords: Teaching Methods, Learning Motivation, Nursing Students. ABSTRAK Metode mengajar merupakan cara yang dipergunakan oleh dosen seorang dosen dalam mengadakan hubungan dengan mahasiswa pada saat berlangsungnya pengajaran. Penelitian ini bertujuan untuk mengetahui hubungan metode mengajar dosen terhadap motivasi belajar mahasiswa DIII Keperawatan AKPER Hermina Manggala Husada Jakarta. Desain penelitian menggunakan pendekatan cross sectional. Teknik pengambilan sampel menggunakan teknik purposive sampling. Jumlah sampel dalam penelitian ini 270 responden. Analisis yang digunakan adalah analisis univariat dan bivariat. Hasil analisis bivariat menunjukkan terdapat hubungan antara metode mengajar berdasarkan pemberian informasi dengan motivasi belajar intrinsik mahasiswa DIII Keperawatan dan terdapat hubungan antara metode mengajar berdasarkan pemberian informasi dengan motivasi belajar ekstrinsik mahasiswa DIII Keperawatan. Terdapat hubungan antara metode mengajar berdasarkan pemecahan masalah dengan motivasi belajar instrinsik mahasiswa DIII Keperawatan dan terdapat hubungan antara metode mengajar berdasarkan pemecehan masalah dengan motivasi belajar ekstrinsik mahasiswa DIII Keperawatan. Terdapat hubungan antara metode mengajar berdasarkan penugasan dengan motivasi belajar instrinsik mahasiswa DIII Keperawatan dan terdapat hubungan antara metode mengajar berdasarkan penugasan dengan motivasi belajar ekstrinsik mahasiswa DIII Keperawatan di AKPER Hermina Manggala Husada Jakarta. Pengembangan kurikulum perkuliahan dan mengefektifkan metode mengajar dalam proses pembelajaran penting untuk meningkatkan motivasi belajar mahasiswa. Kata Kunci: Metode Mengajar, Motivasi Belajar, Mahasiswa Keperawatan